2017
DOI: 10.1089/mdr.2016.0085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum β-Lactamases CTX-M-8 and CTX-M-2-Producing Salmonella Serotypes from Clinical and Nonhuman Isolates in Brazil

Abstract: We characterized extended-spectrum β-lactamases (ESBL) enzymes among Salmonella strains isolated in Brazil from 2009 to 2014. Salmonella recovered from both clinical and nonhuman (food, poultry, and environment) sources were subjected to antimicrobial susceptibility testing. β-lactamases genes were detected by polymerase chain reaction/sequencing; plasmid profiles and transferability were assessed by S1-pulsed field gel electrophoresis (PFGE). Genetic diversity was evaluated by XbaI-PFGE. Out of 630 Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Researchers studying different types of salads in Portugal and Switzerland have reported that RTE food pathogens share the same ESBL genes as clinical isolates collected from hospital patients, suggesting the potential for commensal bacteria to act as antibiotic-resistant gene reservoirs, especially in hospital settings 9 , 20 . Further, ESBL-producing Enterobacteriaceae isolates have been reported in beef burger, seafood, and raw vegetable samples 15 , 31 , 32 . Based on these reports, ESBL gene sources in human food chains include both RTE and non-RTE food products.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers studying different types of salads in Portugal and Switzerland have reported that RTE food pathogens share the same ESBL genes as clinical isolates collected from hospital patients, suggesting the potential for commensal bacteria to act as antibiotic-resistant gene reservoirs, especially in hospital settings 9 , 20 . Further, ESBL-producing Enterobacteriaceae isolates have been reported in beef burger, seafood, and raw vegetable samples 15 , 31 , 32 . Based on these reports, ESBL gene sources in human food chains include both RTE and non-RTE food products.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 describes the source, geographic location of sampling, and bla genes found in studies that reported ESBL and pAmpC-encoding genes in food or food-producing animals in Brazil. In Salmonella, bla CTX-M-2 was identified in non-transferable and conjugative plasmids of 90 to 290 kb. These plasmids belonged to IncI1, IncHI2, or non-typable incompatibility groups [36,145,155,156]. Part of isolates characterized by Fernandes and coworkers was not able to transfer bla CTX-M-2 to E. coli, suggesting a possible chromosomal location of this gene [145].…”
Section: Streptococcus Sppmentioning
confidence: 94%
“…Studies indicate that these genes are mainly carried by E. coli and nontyphoid Salmonella, but also by Escherichia fergusonii, Klebsiella pneumoniae, Citrobacter diversus, and Proteus mirabilis [136][137][138][139][140]. Reports include animals on farms [36,[136][137][138][141][142][143][144][145][146][147], whole carcasses, or meat pieces available in Brazilian retail markets [69,136,138,140,145,148,149], and exported chicken meat [150][151][152]. The same genes were detected in turkeys with clinical signs of colibacillosis [153].…”
Section: Streptococcus Sppmentioning
confidence: 99%
See 2 more Smart Citations